Integrität und Verantwortung: Hannah Arendts Konzept der Rechtspersonalität und die Zerstörung der Person im Nationalsozialismus - Bushart, Barbara (transcript, 2019)
The volume is a legal-theoretical investigation of the significance of the concept of personality in Hannah Arendt's political philosophy.